Soldiers of the old army - Vogel, Victor, 1909-2004 (Texas A & M University military history series, 1990)
Between the two world wars, the United States Army was "a school, an athletic club, an orphan's home, and a boy's camp." That description of Victor Vogel's "old army", in which he enlisted as a private in 1934, gives a small hint at how old-fashioned the army was in an age of isolationism and meager congressional appropriations. In the pre-World War II army, cavalry troops were still mounted, horses pulled artillery carriages, and mules pulled supply wagons. The soldiers' basic weapon was the Springfield rifle, which was virtually an enemy itself as the men learned to fight its vicious recoil. The starting pay for a private was twenty-one dollars, and between 1922 and 1942 that sum did not increase, nor did base pay for men of any rank, and promotions were few and far between